The Influence of Product Quality, Prices, and Promotions on Customer Satisfaction Through Purchasing Decisions as Intervening Variables for Women's Clothing Customers in The Shopee Market Place, Surabaya City - Alifa Novi Firdausi; Rina Sulistiyani (Sinergi : Jurnal Ilmiah Ilmu Manajemen, 2024)
The Modernization Era has made activities move to the digital realm. Shopee is the main marketplace in Indonesia, with the most site visits throughout 2022, around 200 million visitors. The data sources used are primary and secondary data. The data collection technique is a questionnaire. Data was collected via questionnaire, data analysis was carried out using Structural Equation Modeling (SEM) Partial Least Square (PLS). The research results show that product quality, price, and promotion have a significant effect on purchasing decisions. Product prices and promotions have a significant effect on customer satisfaction in the Surabaya City Shopee marketplace. Product quality, price, and product promotion do not affect customer satisfaction through purchasing decisions. Purchasing decisions do not affect customer satisfaction.